Inovasi Pembelajaran Fiqih Berbasis Kecerdasan Buatan untuk Santri Multigenerasi di Pondok Pesantren Darul Hidayah Madani Kota Lubuklinggau - Dilla Anggela; Dimas Putra Andika (Prodi PGMI Universitas Islam Nusantara Al-Azhaar Lubuklinggau, 2026)
The advancement of Artificial Intelligence (AI) technology has triggered massive changes in the field of education, particularly in Islamic education within Islamic boarding schools (pondok pesantren). As traditional educational institutions, Islamic boarding schools are currently facing various new challenges in meeting the needs of multigenerational students who have different learning styles. This study aims to evaluate innovations in fiqh learning using artificial intelligence, especially for multigenerational students at Pondok Pesantren Darul Hidayah Madani. The method used in this study is a qualitative approach with a case study design. Data collection was carried out through observation, interviews, and documentation techniques. The results of this study indicate that the implementation of artificial intelligence-based fiqh learning can improve students' understanding, increase learning motivation, and meet the educational needs of students from different generations. This innovation includes the implementation of fiqh chatbots, the use of AI-supported interactive learning media, automated learning evaluation systems, and personalized learning methods. The implementation of this innovation continues to maintain the values of Islamic boarding schools and strengthens students' understanding of fiqh in a relevant and practical manner. Keywords: Artificial Intelligence (AI), Fiqh Learning, Islamic Boarding School, Multigenerational Students, Educational Innovation